Music students’ experienced workload in higher education : A systematic review and recommendations for good practice - Jääskeläinen, Tuula; López-Íñiguez, Guadalupe; Phillips, Michelle (SAGE, 2022)
While there is extensive research on student workload in higher education, research-based findings relating to music students’ workloads are, to a great extent, lacking. In this study, we aim to review the literature systematically (a) to identify the factors that have an impact on students’ experiences of workload (experienced workload) and (b) to better understand music students’ experiences of their workloads in relation to their studies. The overall aim is to offer recommendations for students, teachers, administrators, and student health and well-being services as to how to deal with music students’ workload. We conducted a systematic search of literature in 23 electronic databases and 19 music research journals following the Preferred Reporting Items for Systematic Reviews guidelines. Eligibility criteria consisted of design, sample, phenomenon of interest, evaluation, and type of research. Twenty-nine qualitative, quantitative, and multistrategy studies fulfilled the inclusion criteria. Data were extracted and the quality of the studies was appraised. Extended meta-ethnography was used to create a synthesis revealing specific themes offering recommendations for good practice to (a) increase music students’ ability to cope with their workload, (b) provide tools for teachers to support music students to manage and cope with workload, and (c) develop learner-centered environments in higher music education. In addition to presenting recommendations for good practice, we conclude that more research using high-quality designs is needed to investigate music students’ discipline-specific experienced workload.
Keywords: musiikki; opiskelijat; korkeakouluopiskelu; psyykkinen kuormittavuus; oppiminen; systemaattiset kirjallisuuskatsaukset